Keanekaragaman tumbuhan Kebun Raya Mangrove Gunung Anyar Surabaya - Wulandari, Adelia; Irawanto, Rony (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Abstract: Mangroves are ecosystems by tree-dominated on intertidal zones. Surabaya efforts to preserve the mangrove area with developing a mangrove botanic garden, namely the Mangrove Botanic Garden - Gunung Anyar Surabaya. This research aims to carry out an inventory of plant diversity in the Mangrove Botanic Garden - Gunung Anyar Surabaya. The research is field exploration, recording directly in the field the species of mangrove plants found. Apart from that, plant diversity was obtained based on reports from agencies and previous research references, then descriptive analysis was carried out in tabular form. The research results show that the Mangrove Botanic Garden has a collection of around 57 species of mangrove plants with a total land area of ​​34 hectares on Gunung Anyar, Medokan Sawah and Wonorejo. From the results of the previous study, in 2012 there were 41 species recorded, in 2017 there were 46 species recorded, in 2018 there were 47 species recorded, in 2020 there were 47 species recorded, in 2022 there were 25 species recorded and in 2023 there were 16 species recorded in the Mangrove Botanic Garden - Gunung Anyar Surabaya as plant collection. So a total of 88 species of mangrove plants are currently recorded. This shows that there has been a change with the increase 20 species of plant, but only 4 species are true mangroves, the others 16 speceis are associated plants in the mangrove area. Keywords: Inventory ; Botanic Garden ; Mangroves ; Surabaya